Configurations of web services - Barbosa, Marco António (2007)
The quest for sound foundations for the orchestration of web services is still open. To a great extent its relevance comes from the possibility of defining formal semantics for new language standards (like BPEL4WS or WS-CDL) in this emerging and challenging technology. As a step in that direction, this paper resorts to a notion of configuration, developed by the authors in the context of a Reo-like exogenous coordination model for software components, to formally express service orchestration. The latter is regarded as involving both the architectural assembly of independent services and the description of their interactions.